2014
DOI: 10.1007/s11999-013-3240-z
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Nailing for Pediatric Subtrochanteric and Supracondylar Femur Fractures

Abstract: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 27 publications
2
49
0
2
Order By: Relevance
“…[ 1 , 9 , 10 ] With the development of surgical technology, the operative indication of TEN has gradually extended to the proximal femur 1/3 and subtrochanteric fractures. [ 3 , 11 ] However, several studies have demonstrated suboptimal results with fractures in the proximal third of the femur [ 1 , 9 ] and length-unstable fracture patterns. [ 3 , 12 ] In the series by Flynn et al, [ 1 ] the only patient with a poor Titanium Elastic Nails Outcome Score was an 11-year-old child with a proximal, oblique comminuted fracture that healed with 15 mm of shortening and 20° of varus angulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 , 9 , 10 ] With the development of surgical technology, the operative indication of TEN has gradually extended to the proximal femur 1/3 and subtrochanteric fractures. [ 3 , 11 ] However, several studies have demonstrated suboptimal results with fractures in the proximal third of the femur [ 1 , 9 ] and length-unstable fracture patterns. [ 3 , 12 ] In the series by Flynn et al, [ 1 ] the only patient with a poor Titanium Elastic Nails Outcome Score was an 11-year-old child with a proximal, oblique comminuted fracture that healed with 15 mm of shortening and 20° of varus angulation.…”
Section: Discussionmentioning
confidence: 99%
“…But according to their study, open plating and submuscular plating were not analyzed separately, which may amplify the excellent results. Parikh et al [ 11 ] recently demonstrated that the outcomes of 33 patients with subtrochanteric fractures in school-age treated by TEN were satisfactory. Major complications such as nonunion, malunion, or limb length discrepancy and other serious complications after operation were low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indications of ESIN in humeral fractures vary depending on the fracture site: the proximal metaphysis or the diaphysis. In the fractures of the surgical neck of the humerus, ESIN is indicated because it reduces the period of immobilization required in the case of conservative treatment [ 6 , 9 12 ].…”
Section: Humeral Fracturesmentioning
confidence: 99%
“…At the end of the operation, the nails are cut and hidden under the tegument, without causing local irritations, so as to be easily visible at the time of ablation [ 2 , 6 , 10 ].…”
Section: Humeral Fracturesmentioning
confidence: 99%